Peningkatan Kompetensi Penulisan Karya Ilmiah Bagi Pengajar Bipa Di Yala Rajabath University Thailand - Andajani, Kusubakti; Pratiwi, Yuni; Syahri, Moch; Widyartono, Didin; Martutik, Martutik (STIE Malangkucecwara, 2023)
Teachers are required to have various competencies in the process of transferring knowledge to their students, as are BIPA teachers. Quality teaching competency is an important aspect in the successful achievement of student competency. Therefore, discussions on teacher competence are important as supporting the success of second language learning, in the context that will be carried out, namely the competence of BIPA teachers in writing scientific papers. This is done because writing skills are skills that are difficult to learn and teach. Additionally, consider BIPA which is increasingly popular for non-native speakers to follow. The objectives of this PKM are (1) to provide training in an effort to increase the competency in writing scientific papers of BIPA teachers, (2) to provide insight related to the use of technology in writing scientific papers. This activity was carried out at Yala Rajabhat University, Thailand. This location was chosen because it held BIPA learning and there were problems regarding inadequate insight in writing scientific papers in the context of Indonesian language and culture.The solution offered is to provide academic writing material (1) paraphrasing and quoting skills, (2) word or lexical variations, (3) active and inactive sentences, (4) thinking processes which include ability to understand written information, (5) structure and development of arguments in micro and macro stages. In addition, to achieve the second goal, provide insights related to the use of Mendeley, Vos Viewer, and Sciendiret and Scihub. It is hoped that these two indicators will be able to solve the problems faced by BIPA teachers